Effect of immersion time in mouthwash on the flexural strength of polyethylene fiber-reinforced composite - Akmal, Syazwani; Siswomihardjo, Widowati; Sunarintyas, Siti (Faculty of Dentistry, Universitas Gadjah Mada, 2020)
Fiber-reinforced composite (FRC) fixed dentures are exposed to various oral environments. One of the ways in maintaining good oral condition is by using mouthwash. Questions have been araised about the safety of prolongeduse of mouthwash towards FRC. The aim of this study was to evaluate the effect of immersion time in mouthwash on the flexural strength of polyethylene FRC. The specimens used were polyethylene FRC (Construct, KerrLab, USA) and flowable composite resin (Master Flow Biodinamica, Brazil). Block shaped specimens (2x2x25 mm) was light cured (n=12). Specimens were divided into threek groups of immersion: Group 1 (without immersion); Group 2 (24 hour immersion); Group 3 (48 hour immersion). The mouthwash used was Listerine Multi-Protect (Johnson & Johnson, Indonesia) (21.6% alcohol content). Flexure strength was measured by Universal Testing Machine. The results showed the average strength value (MPa) for Group 1 was 91.318 ± 12.466, Group 2 was 62.253 ± 8.027, and Group 3 was55.033 ± 3.373. Statistical analysis (ANOVA) showed that immersion time in mouthwash influenced the flexural strength of polyethylene FRC (p<0.05). LSD0.05 showed there were significant differences of flexural strength between Group1-Group 2, Group 1-Group 3 but not for Group 2-Group 3. In conclusion, the flexural strength of polyethylene FRC were decreased by the immersion time in mouthwash.